2019
DOI: 10.1039/c9bm00964g
|View full text |Cite
|
Sign up to set email alerts
|

The sulfation of biomimetic glycosaminoglycan substrates controls binding of growth factors and subsequent neural and glial cell growth

Abstract: This work shows that alginates can be sulfated to engineer defined substrates that control growth factor binding and neural growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 76 publications
0
22
1
Order By: Relevance
“…We and others have shown earlier that increasing the sulfation of biomimetic sulfated GAGs enhances the growth of chondrocytes [36,59], neural cell lines [43], and fibroblasts [60], which is in contradiction with the finding of the current study that showed a decrease in cell growth. The discrepancy in results between the current study and the previous ones can be explained by the fact that previous studies used sulfated polysaccharides stabilized to a substrate whether in 2D or 3D unlike the current study where AlgSulf n were added in solution [36,43]. Sulfated polysaccharides used in previous studies were sterically less mobile while in the current study they might encapsulate growth factors, making them unavailable for GF receptors on the cell surface.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We and others have shown earlier that increasing the sulfation of biomimetic sulfated GAGs enhances the growth of chondrocytes [36,59], neural cell lines [43], and fibroblasts [60], which is in contradiction with the finding of the current study that showed a decrease in cell growth. The discrepancy in results between the current study and the previous ones can be explained by the fact that previous studies used sulfated polysaccharides stabilized to a substrate whether in 2D or 3D unlike the current study where AlgSulf n were added in solution [36,43]. Sulfated polysaccharides used in previous studies were sterically less mobile while in the current study they might encapsulate growth factors, making them unavailable for GF receptors on the cell surface.…”
Section: Discussioncontrasting
confidence: 99%
“…GF binding is critical for multiple cellular events, including proliferation, differentiation, and migration. This makes sulfation pivotal for normal cell growth, for example in wound healing and regeneration, but also for cancer cell growth and metastasis [29,36,43]. Biomimetic sulfated GAGs also showed proliferative effects on normal chondrocytes [36] and neural cell lines [43] possibly through increased GF binding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, sAlg with DS = 1.0 showed a higher degree of interaction with FGF‐2 compared with DS = 1.4, attributed to a higher relative chain flexibility. [ 271 ] This was not observed for interaction studies of sAlg in solution or in layer‐by‐layer films, where a similarly high DS resulted in the highest degree of FGF‐2 binding. [ 272 ] Recently, release of growth factors from nanofibrous and printed structures based on sAlg has been investigated.…”
Section: Biological Properties and Biomedical Applications Of Espsmentioning
confidence: 99%
“…Chemoattractants, such as growth factors and chemokines, play crucial roles in situ cell recruitment (Zhang et al, 2020). They can be delivered into local defect areas by being simply injected alone or loaded within scaffold matrix (Chuma et al, 2004;Malaeb et al, 2019). However, the use of these bioactive factors may result in some undesirable side-effects (van Beuningen et al, 2000;Miller et al, 2010).…”
Section: Introductionmentioning
confidence: 99%